A Wooly Way? Fiber technologies and cultures 3,000-years-ago along the Inner Asian Mountain Corridor - Doumani Dupuy, Paula N.; Tabaldiev, Kubatbek; Matuzeviciute, Giedre Motuzaite (Frontiers in Ecology and Evolution, 2023)
Wool-focused economies yielded a pastoralist materiality that visibly shaped the material and lived experiences of Central Asian populations today. In this paper, we investigate the earlier application of fibers through a key mountain corridor for social interactions during the Bronze Age. We focus on the site of Chap 1 located in the highlands of the Tien Shan Mountains of Kyrgyzstan where researchers have found a complex agropastoral subsistence culture was established from at least ca. 3000 BCE. The perishable materials that would have accompanied the early spread of cultural and technological traditions related to fiber-based crafts throughout this area are under-documented due to poor organic preservation. Hence, there has been little consideration of the role that textiles played in highland occupation and how woven fabrics might have facilitated settlement in the extreme climates of Central Asia. We address this ongoing problem through a multi-application survey of Chap’s unpublished textile evidence preserved as impressions in coarseware ceramics of its Final Bronze Age. We consider evidence that sheep wool formed a key cultural adaptation for surviving the extreme winters of Central Asia’s highland regions.